2017
DOI: 10.1590/s1517-707620170002.0164
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de compósitos particulados de polietileno de alta densidade/pó de concha de molusco

Abstract: RESUMO O objetivo deste trabalho foi investigar as propriedades térmicas, mecânicas e termo dinâmico mecânicas de compósitos de polietileno de alta densidade (PEAD) com a incorporação do pó de conchas de moluscos (5, 10 e 20% em peso). A matriz pura e seus compósitos foram misturados em um misturador interno e em seguida moldados por compressão. A incorporação do pó de concha de molusco diminuiu o índice de fluidez do PEAD em uma faixa de 23 a 53%, já a cristalinidade da matriz praticamente não foi alterada. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…It is observed that the increase in the amount of leather powder is directly proportional to the increase in the interfacial adhesion of these composites. The fracture surface morphologies of the composites in Figures 5A, 5B and 5C, as verified in the study by Firmino et al (2017), showed that the particle size of the reinforcement material is inversely proportional to its effective performance in the reference matrix. In this way, it is proved that the compacting of the material before extrusion aims to decrease the volume, being efficient to increase the homogeneity of the composites, due to the ease of fusing the materials used in the manufacture of the bodies, making them more resistant composites in relation to the reference matrix, as seen in the mechanical results.…”
Section: Scanning Electron Microscopysupporting
confidence: 63%
“…It is observed that the increase in the amount of leather powder is directly proportional to the increase in the interfacial adhesion of these composites. The fracture surface morphologies of the composites in Figures 5A, 5B and 5C, as verified in the study by Firmino et al (2017), showed that the particle size of the reinforcement material is inversely proportional to its effective performance in the reference matrix. In this way, it is proved that the compacting of the material before extrusion aims to decrease the volume, being efficient to increase the homogeneity of the composites, due to the ease of fusing the materials used in the manufacture of the bodies, making them more resistant composites in relation to the reference matrix, as seen in the mechanical results.…”
Section: Scanning Electron Microscopysupporting
confidence: 63%